Analisis Persepsi Pengunjung Terhadap Fasilitas Water Refill di Stasiun Semarang Tawang Jawa Tengah - Siska Ayu Andarini; Agnes Andeli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study is entitled “Analysis of Visitors’ Perceptions of Water Refill Facilities at Semarang Tawang Station, Central Java”. The background of this research stems from the provision of water refill facilities by PT Kereta Api Indonesia as an environmentally friendly innovation that supports sustainable transportation, reduces single-use plastic, and promotes a healthy lifestyle. However, its utilization in the field has not been optimal, as many visitors still prefer bottled water for practicality or due to doubts about water quality. The study employed a descriptive qualitative method through observation, interviews, and documentation. Data were collected from visitors with diverse backgrounds as well as station staff. The findings show that the water refill facility at Semarang Tawang Station generally meets standards of cleanliness and comfort, with clear water, well-functioning dispensers, and a relatively clean environment. Nevertheless, some weaknesses remain, such as wet and slippery floors, locations that are less visible due to the absence of clear signs, and dispenser designs that are not child-friendly. Low utilization is also influenced by limited information about the facilities, visitors habits that favor bottled water, and perceptions of quality that remain doubtful despite meeting laboratory standards. Technical obstacles such as malfunctioning taps or water depletion occur infrequently but still reduce user trust. In conclusion, the water refill facility has great potential to support sustainable public services, yet its success depends on the combination of technical quality, visitors trust, and the effectiveness of socialization carried out by station management.